The role of pyruvate dehydrogenase in the lifespan determination of daphnids - Wenkai Chen; Xueying Xu; Zhidan Zeng; Mingsen Zhou; Jiying Chen; Guangfu Hu; Anfu Shen; Dapeng Li; Liu Xiangjiang (Nature Communications)
Abstract The general association between longevity and energy metabolism has been well-documented for some time, yet the specific metabolic processes that regulate longevity remain largely unexplored. In contrast to the common active swimming daphnids (e.g., Daphnia sinensis), Simocephalus vetulus is notable for being sedentary and having a lower metabolic rate, yet it has a longer lifespan than D. sinensis. In this study, metabolomic analysis and drug validation experiments are employed to demonstrate that the lower pyruvate dehydrogenase (PDH) activity reduces the locomotor performance of S. vetulus and to identify PDH activity as a regulator of the lifespan of daphnids. Inhibition of PDH activity in daphnids by CPI-613 attenuates its ATP supply and locomotor performance but significantly induces longevity. The study also determines that the invertebrate neurotransmitter octopamine and temperature have a significant impact on PDH activity and modulate daphnids lifespan. And when the effects of temperature and octopamine on PDH activity are counteracted by inhibitors or agonists, the impact on lifespan becomes ineffective. These results support an important role for PDH in lifespan regulation and locomotor performance in daphnids and provide insights into the metabolic regulation of lifespan.